Passive heat maintenance after an initial warm-up improves high-intensity activity during an interchange Rugby League movement simulation protocol - Fairbank, M.; Highton, J.; Twist, C. (The Journal of Strength and Conditioning Research, 2021)
This study examined using passive heat maintenance (PHM) to maintain core temperature after a warm-up and its effect on simulated first half running performance in rugby players. Thirteen male rugby players completed this randomized crossover study. Tympanic temperature was taken before a warm-up and then after a further 15 minutes of passive recovery either with (PHM) or without (CON) a PHM garment. Subjects then completed 23 minutes of the rugby league movement simulation protocol (RLMSP-i). Differences in tympanic temperature were unclear between CON and PHM before (35.7 ± 1.3 cf. 36.0 ± 1.1° C; effect size [ES] = 0.20) and during exercise (34.5 ± 0.1 cf. 35.2 ± 0.1° C; ES = 0.26-0.35). High-intensity running (ES = 0.27) and peak sprint speed were higher (ES = 0.46-0.56) during the PHM compared with the CON trial. Time spent above 20 W·kg-1 also increased in the first quartile of the PHM compared with the CON trial (ES = 0.18). All other between trial comparisons of performance were unclear. HRmean (ES = 0.38) was higher in PHM compared with CON, while differences in RPEmean (ES = -0.19) were unclear. There are small to large increases in high-intensity activity performed during a playing bout when rugby players wear a PHM garment after a warm-up. Rugby players should consider PHM during extended periods between a warm-up and starting a match.